2016
DOI: 10.1371/journal.pone.0161973
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Auger Electron-Induced, Single- and Double-Strand Breaks on Plasmid DNA Caused by 99mTc-Labeled Pyrene Derivatives and the Effect of Bonding Distance

Abstract: It is evident that 99mTc causes radical-mediated DNA damage due to Auger electrons, which were emitted simultaneously with the known γ-emission of 99mTc. We have synthesized a series of new 99mTc-labeled pyrene derivatives with varied distances between the pyrene moiety and the radionuclide. The pyrene motif is a common DNA intercalator and allowed us to test the influence of the radionuclide distance on damages of the DNA helix. In general, pUC 19 plasmid DNA enables the investigation of the unprotected inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
0
23
0
3
Order By: Relevance
“…These studies provided valuable knowledge that illuminated the inverse relationship between AE-emitter distance to the DNA and DNA damage and cell kill ( Kortylewicz et al, 2012 ). Since then, several small molecule DNA intercalators have been proposed as nuclear-targeting agents for AE-emitting radionuclides, such as radiolabeled derivatives of acridine orange ( Pereira et al, 2017 ), pyrene ( Häfliger et al, 2005 ; Reissig et al, 2016 ), doxorubicin ( Imstepf et al, 2015 ), and daunorubicin ( Fondell et al, 2011 ). Acridine orange is a cell-permeable molecule with anticancer drug and radiosensitizing properties.…”
Section: Subcellular Targets For Radionuclide Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…These studies provided valuable knowledge that illuminated the inverse relationship between AE-emitter distance to the DNA and DNA damage and cell kill ( Kortylewicz et al, 2012 ). Since then, several small molecule DNA intercalators have been proposed as nuclear-targeting agents for AE-emitting radionuclides, such as radiolabeled derivatives of acridine orange ( Pereira et al, 2017 ), pyrene ( Häfliger et al, 2005 ; Reissig et al, 2016 ), doxorubicin ( Imstepf et al, 2015 ), and daunorubicin ( Fondell et al, 2011 ). Acridine orange is a cell-permeable molecule with anticancer drug and radiosensitizing properties.…”
Section: Subcellular Targets For Radionuclide Therapymentioning
confidence: 99%
“…The Alberto group explored the effect of 99m Tc-labeled pyrene-NLS (SV40 NLS peptide) conjugates on cell survival and found that these compounds exhibited a DNA damaging effect, leading to mitotic catastrophe ( Haefliger et al, 2005 ). Reissig et al (2016) synthesized related pyrene constructs with 99m Tc-labeled alkyne groups of variable length. In cell-free studies, they showed a decrease in DNA damage when the distance between the intercalating moiety was increased from 0.3 to 1.5 nm, clearly demonstrating the need for close association with DNA molecules for AE-generated DNA lesion formation.…”
Section: Subcellular Targets For Radionuclide Therapymentioning
confidence: 99%
“…Es konnte weiterhin nachgewiesen werden, dass Tc-99m-markiertes DAPI an die DNA bindet und dosisabhängig ESB und DSB induziert, welche durch den Radikalfänger DMSO nicht verhindert werden können und somit auf eine direkte Wechselwirkung und nicht auf eine indirekte, Radikal-vermittelte Wirkung zurückgehen [8]. In einer Folgeuntersuchung wurde der Abstand des Radioisotops zur Bindungsstelle variiert, so dass bei zunehmender Entfernung der Anteil an DSB rückläufig war und die DNA-Schäden durch DMSO effektiv verhindert werden konnten [9]. Außerdem konnte gezeigt werden, dass der Alphastrahler Ra223 im Vergleich zu Re-188 und Tc-99m ebenfalls primär Radikal-vermittelte schädigende Wirkung hat [15].…”
Section: Diskussionunclassified
“…7 Darstellung der relativen Anteile der Fluoreszenzintensität der OC-Konformation (ESB) und der L-Konformation (DSB) bei Bestrahlung mit 200 Gy Röntgenstrahlung in Abhängigkeit von der PI-Konzentration (MW aus 3 Versuchen ± SEM). mehr zeigen können [9]. Es lässt sich auch damit begründen, dass PI eine ionische Verbindung ist und zumindest ein großer Teil des Iodids in der wässrigen Lösung frei vorliegt.…”
Section: Diskussionunclassified
See 1 more Smart Citation